Resistance in Poetry of Atif Tauqeer - Alvi, Qamar Abbas; Haq, Ihtisham ul; Rahman, Muhammad (sourcecoder, 2023)
Atif Tauqeer is a Pakistani poet of 21st century, he was born in Jehlum (Punjab, Pakistan) after completing his education he selected Journalism as profession and moved to Europe. Radd is his first collection of poetry that was published in 2022. Love, Resistance, class conflict, violence and forceful disappearance are the major topics of his poetry.